The vocative style in Arabic and Indonesian languages: A contrastive analytical study - Fithri, Chusna Nazilatul; Maskud, Maskud; Maulana, Asep (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
The call (an-nida) is a fundamental form of human communication that signifies the need for interaction among individuals. Calling methods vary between languages, reflecting diverse cultural values and impacting language understanding and cross-cultural interaction. The researcher chose qualitative research and followed the descriptive-analytical approach, using the introspective approach in data collection. When analyzing the data, she relied on the comparative analysis method. One of the key findings of this research is that the call in Arabic and Indonesian shows both similarities and differences. Each language uses tools for calling, including a common tool for general calls, which is